How sleep quality affects activities of daily living in Parkinson’s disease: the mediating role of disease severity and the moderating role of cognition - Luo, Yajun; Liu, Junyi; Chen, Dongqin; Liu, Manhua; Yuan, Yuan; Hu, Jingzhe; Wu, Jiayu; Wang, Fen; Liu, Chunfeng; Chen, Juping; Mao, Chengjie (Frontiers in Aging Neuroscience, 2023)
Objective: The aim of this study was to explore the influential mechanism of the relationship between sleep quality and activities of daily living (ADL) in patients with Parkinson's disease (PD), we hypothesized disease severity as a mediator and assumed the mediating process was regulated by cognition. Methods: 194 individuals with PD (95 women and 99 men) were enrolled in study. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality of PD patients. Patients’ ADL, disease severity and cognition were measured by the Unified Parkinson's Disease Rating Scale-II (UPDRSII), Hoehn-Yahr (H-Y) Scale, and Mini-Mental State Examination (MMSE). We investigated the mediating role of disease severity and the moderating effect of cognition on the association between sleep quality and ADL in PD patients. Results: The score of UPDRSII was positively correlated with the score of PSQI and H-Y stage, while the score of MMSE was negatively correlated with the score of H-Y stage and UPDRSII. Sleep quality predicts disease severity, and disease severity predicts ADL. Disease severity mediated the relationship between sleep quality and ADL, and the mediating effect was 0.179. Cognition alone did not affect ADL, but the interaction between disease severity and cognition was significantly affected ADL, confirming the moderating effect of cognition in PD patients. Conclusions: Disease severity mediated the association between sleep quality and ADL, good cognition significantly reduced disease severity’s mediating influence on the relationship between sleep quality and ADL. Our study indicated a close relationship between ADL and sleep and cognition in PD, and also provided new insights into the overall management of PD and a better quality of life of PD patients.